Tribal folklore :a study on Kuvis (Kandhas) of Koraput - Jagannath Rath (Concept, 2019)
Though the tribals are the aboriginals and indigenous people, still they possess a rich culture. The tribal people express their cultural identity in their social and political organizations, language, rituals, festivals, dress pattern, ornaments, technology, art and craft. They have mostly a folk culture. This book is on the folklore of Kandhas. The largest tribal group among the 62 tribes in Odisha. Folklore is the rich oral literature of the tribals in general and that of the Kandhas in particular. The author has collected some of the folk aspects of the Kandhas (Kuvis) through their myths, proverbs, songs, stories etc. Efforts have been made to highlight socioeconomic and religious importance and human values contained in the folklore of the tribe concerned. It is hoped that the present work will provide intellectual feedback to the academicians, scholars and others who are interested to know about the tribal culture, particularly their folklores.